KESEPAKATAN COMFORT WOMEN PADA TAHUN 2015 SEBAGAI INSTRUMEN JEPANG DALAM MENCAPAI KEPENTINGAN KEAMANANNYA - Pavita, Putu Rania; Sushanti, Sukma; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT Japan’s unwillingness to acknowledge their military’s involvement in the implementation of the comfort women system during the World War II has dealt a negative impact upon their foreign relations, especially with South Korea. This research aims to discover how Japan used the 2015 comfort women agreement as an instrument to achieve its security interests using namely two concepts; Japan’s Security Interests in its Grand Strategy and Diplomacy in Statecraft. Within the process of this research it is discovered that Japan has a security interest in tackling the North Korea and Chinese threat in the Asia Pacific region. Japan used the 2015 Comfort women Agreement as an instrument to achieve its security interests by restoring its diplomatic relations with South Korea and tightening its alliance with the United States in order to face the two threats to their national security. Keywords: Comfort women Agreement, Japan, Security Interests, Japan’s Grand Strategy, Diplomacy in Statecraft